Fundamental frequency model of a dynamic voltage restorer - Iyer R.K.; Ramasamy A.K.; Ramachandaramuthy V.K.; Murkerjee R.N. (2023)
This paper encompasses the fundamental frequency model of a Dynamic Voltage Restorer (DVR) based on a voltage source converter (VSC) with IGBT switches. Using basic circuit analysis and Matlab simulation program, a simple single-phase circuit model is obtained to assist in analyzing the component parameters of the circuit with various load power factor and voltage sag with phase jump. The fundamental frequency model is obtained assuming negligible effect of harmonics and balanced three-phase voltage sag. This model would introduce a relationship between the desired injected voltage vector and the actual injection voltage vector. This relationship is defined as the correction factor, K. This factor will provide the compensation necessary to produce an accurate injected voltage vector taking into account the voltage drops and phase shifts caused by the filter elements and transformer connected between the voltage source converter (VSC) and the load. 2005 IEEE.